2012
DOI: 10.21041/ra.v2i3.37
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing two different data processing strategies for monitoring concrete structures using ultrasonic pulse velocity

Abstract: RESUMENO crescente aumento dos sintomas de deterioração precoce em estruturas de concreto serve de argumento para o desenvolvimento e validação de técnicas de monitoramento do estado de conservação das mesmas. Além disto, fornecerem dados para estimar a vida útil das estruturas. A utilização de Ensaios Não Destrutivos permite a prevenção e o controle da deterioração de estruturas de concreto, sem danificar o material. O ensaio de Velocidade de Propagação do Pulso Ultrassônico (VPU) é uma forma bastante eficaz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Exactly for this potentiality, the UPV has been the most investigated NDT in research in Structural Tests and Materials Laboratory of the Federal University of Rio Grande do Sul (LEME/UFRGS). In various research work conducted, on the field and in the laboratory, a technique of UPV was developed, mapping with indirect readings, and confirmed that the method, when properly employed, can offer ease of implementation, fast and suitable fault detection capability [3,4,5,6,7,8,9]. Several researches related to UPV and concrete.…”
Section: Introductionmentioning
confidence: 94%
“…Exactly for this potentiality, the UPV has been the most investigated NDT in research in Structural Tests and Materials Laboratory of the Federal University of Rio Grande do Sul (LEME/UFRGS). In various research work conducted, on the field and in the laboratory, a technique of UPV was developed, mapping with indirect readings, and confirmed that the method, when properly employed, can offer ease of implementation, fast and suitable fault detection capability [3,4,5,6,7,8,9]. Several researches related to UPV and concrete.…”
Section: Introductionmentioning
confidence: 94%
“…UPV propagation at concrete is very sensitive to the presence of flaws, cracks, or other discontinuities. The mapping was performed by indirect measurement technique which has proved appropriate to map the surfaces, allowing to detect voids and defects (Lorenzi, Reginato, Favero & Silva Filho, 2013), (Lorenzi, Caetano, Drunn & Silva Filho, 2003), (Lorenzi, Silva Filho, Caetano, Campagnolo & Strieder, 2004), (Lorenzi, Caetano & Silva Filho, 2005), (Lorenzi, Silva Filho, Campagnolo, Caetano & Fischer, 2006), (Lorenzi, Caetano, Campagnolo & Silva Filho, 2009), (Lorenzi, Lorenzi, Caetano & Silva Filho, 2010), (Lorenzi, Silva Filho, Campagnolo & Caetano, 2012), (Lorenzi, Silva Filho, Caetano & Chies, 2014), (Lorenzi, Caetano, Campagnolo, Lorenzi & Silva Filho, 2015).…”
Section: The Use Of Ultrasonic Tests and Image Analysis For Concrete Monitoringmentioning
confidence: 99%
“…This technique is the oldest of the NDT method for determine crack depth (Zoidis et al, 2013) based on the stress wave propagation technique by measuring the travel time of a compressional wave over a known path length. Due to the C P depends on the elastic constants and the mass density, it is possible to determine the uniformity or integrity of the concrete (Lorenzi et al, 2015). The testing principle is showed in Figure 5 below which represents different cases of ultrasonic pulses from one side to the other side.…”
Section: ) Ultrasonic Through Transmission / Ultrasonic Pulse Velocit...mentioning
confidence: 99%
“…The indirect and semi-direct mode results between the travel time and the distance between transducers which could be an error from point shifting; however, they are required to assess only side or corner of the structure which suitable with slabs, walls, and wider testing areas. The UPV method is an simple method for locating the defected area which have difference of concrete quality by creating the UPV contour mapping (Lorenzi et al, 2015). Nevertheless, the limitations of the UPV method need to access both sides of the structure surface, need smooth surface or using grease coupling for more accuracy, and cannot provide the depth of defects.…”
Section: ) Ultrasonic Through Transmission / Ultrasonic Pulse Velocit...mentioning
confidence: 99%
See 1 more Smart Citation